2020
DOI: 10.21608/ejpt.2020.33415.1009
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Laser Therapy on Pain in Patients With Myofascial Trigger Points

Abstract: Purpose: to investigate the effect of high intensity laser therapy on pain intensity in patients with acute cervical myofascial trigger points in the upper trapezius muscle. Methods: 50 patients (32 female and 18 male) suffering from myofascial trigger points in the upper trapezius muscle participated in this study. They were all recruited from the out-clinic of the faculty of physical therapy Badr university. Their ages ranged from 20 to 40 years old with body mass index less than 25 kg/m². They were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…the results indicate that 66.6% of the articles (n = 2) demonstrate high quality based on internal validity, with PEDro scores equal to or greater than five [22]. As the study by Ahmed et al was not in the PEDro database, it was evaluated and scored four points by the researchers [30].…”
Section: Pedro and Rob2 Assessment For Individual Rctsmentioning
confidence: 99%
See 3 more Smart Citations
“…the results indicate that 66.6% of the articles (n = 2) demonstrate high quality based on internal validity, with PEDro scores equal to or greater than five [22]. As the study by Ahmed et al was not in the PEDro database, it was evaluated and scored four points by the researchers [30].…”
Section: Pedro and Rob2 Assessment For Individual Rctsmentioning
confidence: 99%
“…The randomization process was rated as low risk in 66.7% of the articles [28,29]. The deviations from intended intervention bias was evaluated as high risk in one article [30], some concerns in another [29], and low risk of bias in the other [28], i.e. 33.3% for each category.…”
Section: Pedro and Rob2 Assessment For Individual Rctsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the present study, Hatem et al compared the effects of HILT and physiotherapy (electrical stimulation+ultrasound) on VAS, in patients with the active trigger points of the UT muscle. The authors concluded that HILT significantly reduced pain, compared with physiotherapy [43]. Also, Alayat et al showed that HILT plus pressure release significantly improved the pain intensity and PPT in patients with MTrP in the UT muscle [44].…”
Section: The Effect Of Hilt On the Active Trigger Points Of The Ut Musclementioning
confidence: 99%